Using Qualitative Inquiry to Enhance a Child Neurology Residency. (December 2018) - DiSabella, Marc; Walsh, Heather; Sarnacki, Rachel; Goldman, Ellen
The goal of medical residency programs is to provide educational opportunities to residents to facilitate their transformation into independent and competent health care practitioners. Despite an abundance of quantitative data on resident performance, qualitative data are lacking in published literature. Our study involved a standardized interview with all graduating child neurology residents to better understand their educational experiences during training. Qualitative data analysis resulted in 5 basic themes experienced by all trainees: (1) appreciation for faculty supportiveness, (2) appreciation for faculty receptiveness to feedback, (3) the difficulty of balancing clinical and academic demands during residency, (4) the benefit of structured mentorship and research, and (5) the value of independent and experiential learning. Our findings demonstrate that qualitative inquiry can be used to better understand the educational experience of child neurology residents. The themes identified through this qualitative analysis were useful targets for programmatic quality improvements.